Population structure, floral diversity, habitat geography, and conservation status of Himalayan horse chestnut (Aesculus indica) in western Himalayan moist temperate forest ecosystems of Kashmir region - Irfan, Urwa; Shaheen, Hamayun; Manzoor, Muhammad; Nasar, Sidra; Khan, Raja Waqar Ahmed; Gillani, Syed Waseem; Alrefaei, Abdulwahed Fahad; Attique, Arbaz; Kamal, Asif; Razak, Sarah Abdul; Riaz, Malik Talha (Frontiers in Forests and Global Change, 2025)
This study provides a comprehensive assessment of the population structure, floral diversity, habitat geography, phytosociology, threats, and conservation status of Aesculus indica in the western Himalayan region of Kashmir. This study was designed to investigate distribution patterns, community structure, floristic diversity, and phytosociological attributes of A. indica forests, as well as evaluate the habitat geography of species by using GIS analysis. Primary vegetation data and geographic features were collected via systematic quadrat-based sampling from 14 sites in the moist temperate ecosystem of Kashmir, ranging in elevation from 1,400 to 2,800 m. Population structure analysis revealed an average density of 435.85 stems/ha for A. indica, with a significant variation ranging from 220 to 1,100 stems/ha. The species exhibited a high basal cover of 356.33 cm, emphasizing its significant role in the canopy structure of Himalayan forests. The study identified A. indica as a keystone species supporting a diverse floral community comprised of 168 plant species from 51 families. Dominant families, including Asteraceae, Lamiaceae, Rosaceae, Poaceae, and Polygonaceae, contributed to more than 50% of the total recorded plant species. Phytosociological investigations revealed A. indica to be the dominant species with the highest importance value index (IVI) of 48.81, indicating its ecological significance in temperate forest ecosystems. The species exhibited a preference for north-facing aspects and an altitudinal range of 1,400–2,800 m, which constitute the most suitable habitats for A. indica. However, the study identified significant anthropogenic disturbances, including deforestation, overgrazing, and forest land encroachment, as major threats to A. indica populations in the study area. The deforestation intensity averaged 135 stumps/ha, with some sites exceeding 300 stumps/ha, indicating unsustainable fuelwood consumption patterns and habitat degradation. Overgrazing and trampling were also found to be major threats to A. indica seedlings, affecting the species’ regeneration potential. Conservation strategies should prioritize the protection and restoration of A. indica habitats, especially the upper temperate forest zones with north-facing slopes, to ensure the long-term sustainability of the species. It is recommended to formulate effective conservation measures such as promoting sustainable forest practices, controlling invasive species, restoring degraded habitats, controlled grazing practices, community-based conservation initiatives, sustainable harvesting policies, educating local communities, and promoting alternative livelihoods that support local communities to ensure the preservation of A. indica populations as well as ecosystem health. The study emphasizes the urgent need for effective conservation measures to safeguard A. indica and its associated floral diversity in the western Himalayan region.